Effect of Various Physical Therapy Programs on the Quality of Life, Balance, Kinematics of Speed and Accuracy Movements of the Hand in Patients with Parkinson’s Disease (Baltic Journal of Sport and Health Sciences, 2014)
Research background and hypothesis. Parkinson’s disease is a relevant health problem in the way that the disease limits human movement to a great extent as well as degrades the quality of life and overall communication capabilities. We believe that by accelerating the pace of individual workouts on the treadmill in the gym, better results will be achieved than using individual physical therapy at home.Research aim was to determine the effectiveness of various physical therapy programs on the quality of life, balance and kinematics of speed and accuracy movements of the hand in patients with Parkinson’s disease.Research methods. First group (n = 12) had individual physical therapy in the weightlifting gym. The second group (n = 12) had individual physical therapy at home. For the assessment of the quality of life, we selected the questionnaire PDQ-39 (Parkinson’s Disease Questionaire-39), and the subjects filled it in independently. For the assessment of static and dynamic balance, Berg Balance Scale and balance confidence scale were applied. Walking speed was assessed by using the “Up and go” test. The original device developed by Lithuanian Sports University researchers and Ltd. Katra specialists - the dynamic parameter analyser of human arm and leg movements DPA-1 – was used to evaluate the characteristics of the kinematics of the dominant arm movement.Research results. It was found that after 16 physiotherapy procedures, the quality of life statistically significantly improved in all eight areas (p < 0.05) in both groups under investigation. Mean Berg Balance Scale values after 16 physiotherapy procedures statistically significantly increased (p < 0.05) in Group I and Group II. A statistically significant improvement in balance (p < 0.05) was found in both groups. There was a statistically significant decrease (p < 0.05) in the test performance average time values of “Up and go” test in both groups. A statistically significant increase (p < 0.001) was established in the mean values of the six-minute walk distance. Kinematics of speed and accuracy movements statistically significantly increased (p < 0.05) in both groups.Discussion and conclusions. Both physical therapy programmes were effective in improving the quality of life, balance and kinematics of speed and accuracy movements of the hand in patients with Parkinson’s disease. Individual physical therapy programme at home was less effective, while acceleration of the pace of individual workouts on the treadmill in the gym had a greater impact.Keywords: Parkinson’s disease, quality of life, motor control, physical therapy, reaction time, complexity of task.